The Effect of the Think-Pair-Share Method on the Arabic Reading Skills of Seventh-Grade Students at SMPIT Al-Madinah in Tanjungpinang - Widya Fidiana; Suandi Ali; Muhammad Nur Syahadan; Muhammad Ikhsan Fauzi; Leoni Oktaviani; Ilham Maulana (Diwan Media Pustaka, 2025)
Arabic text reading instruction at the junior secondary level still faces several challenges, particularly in students’ fluency, pronunciation accuracy, meaning comprehension, and active engagement during the learning process. Therefore, a cooperative learning strategy is needed to encourage students to think independently, discuss ideas with peers, and present their understanding actively. This study aims to analyse the effect of implementing the Think-Pair-Share method on the Arabic text-reading skills of seventh-grade students at SMPIT Al-Madinah Tanjungpinang. This research employed a quantitative approach with a one-group pretest-posttest pre-experimental design. The sample consisted of 30 seventh-grade students from the Alexandria class selected through purposive sampling. Data were collected through an oral Arabic reading test, observation, and documentation. The data were analysed using descriptive statistics, the Shapiro–Wilk normality test, the paired-samples t-test, and N-gain analysis with SPSS version 26. The findings show that students’ mean score increased from 46.33 in the pretest to 77.33 in the posttest, indicating a gain of 31.00 points. The hypothesis test produced a significance value of 0.000 < 0.05, indicating a significant difference in students’ reading skills before and after the implementation of the Think-Pair-Share method. The N-gain score of 0.5869 indicates a moderate level of improvement. These findings suggest that the Think-Pair-Share method has a positive effect on students’ Arabic text-reading skills and can be used as an active, collaborative, and meaningful learning strategy.